PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH PEREMPUAN DAN IKLIM MADRASAH TERHADAP MUTU MADRASAH IBTIDAIYAH DI KABUPATEN LIMA PULUH KOTA DAN KOTA PAYAKUMBUH - Susi Sofianti; Hamdi Abdu Karim (STKIP Pesisir Selatan, 2026)
This study aimed to examine the influence of female principals' transformational leadership and school climate on the quality of Islamic elementary schools (Madrasah Ibtidaiyah) in Lima Puluh Kota Regency and Payakumbuh City. The study employed a quantitative approach with a correlational research design. The population consisted of 105 teachers from seven Madrasah Ibtidaiyah led by female principals. A total sampling technique was applied, in which all members of the population were included as research participants. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through simple and multiple linear regression using SPSS version 24. The findings revealed that female principals' transformational leadership did not have a significant partial effect on the quality of Madrasah Ibtidaiyah (Sig. = 0.119 > 0.05). In contrast, school climate had a positive and significant effect on school quality (Sig. = 0.000 < 0.05). Simultaneously, transformational leadership and school climate significantly influenced the quality of Madrasah Ibtidaiyah (Sig. = 0.000), with a coefficient of determination of 77.9%, while the remaining 22.1% was explained by other factors beyond the scope of this study. These findings indicate that improving the quality of Madrasah Ibtidaiyah requires the integration of transformational leadership and a supportive school climate to establish an effective and sustainable educational environment.